Understanding, measuring and utilizing social capital: clarifying concepts and presenting a field application from India - Krishna, Anirudh (International Food Policy Research Institute, 2003)
Social capital is a resource, a propensity for mutually beneficial collective action that communities possess to different extents. Communities with high levels of social capital are able to act together collectively for achieving diverse common objectives. While the concept of social capital is valid universally, the measure of social capital will vary by context. It must be related in each case to aspects of social relations that assist mutually beneficial collective action within that particular cultural context. A locally relevant scale of social capital was developed to assess whether and how social capital mattered for development performance in 69 north Indian villages. Variables corresponding to other bodies of explanation, including extent of commercialization, relative stratification, and relative need were also examined, but a combination of high social capital and capable agency was found to associate most closely with high development performance. Agency is important particularly in situations where institutions are not available that enable citizens to connect with the state and with markets. The productivity of social capital is considerably reduced on account of this institutional gap in the middle. Development performance can be improved in these situations by adding to the stock of social capital and also through enhancing agency capacity.